The Economic Consequences of HIV/AIDS in Southern Africa - Haacker, Markus (IMF Working Papers; Working Paper ;, 2002)
The paper provides an analysis of the impact of HIV/AIDS on the health sector, public education, the supply of labor and the returns to training in nine Southern African countries. Drawing on the preceding sections, it assesses the impact of HIV/AIDS on per capita income in a neoclassical growth framework. HIV/AIDS affects per capita income mainly through its impact of human capital, as measured by the supply of experienced workers. Other factors include the impact on capital accumulation, on education, and on total factor productivity.